2003
DOI: 10.1007/bf03218368
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of binary and ternary blends having the same chemical components and compositions

Abstract: The phase behavior of binary blends of dimethylpolycarbonate-tetramethyl polycarbonate (DMPC-TMPC) copolycarbonates and styrene-acrylonitrile (SAN) copolymers has been examined and then compared with that of DMPC/TMPC/SAN ternary blends having the same chemical components and compositions except that the DMPC and TMPC were present in the form of homopolymers. Both binary and ternary blends were miscible at certain blends compositions, and the miscible blends showed the LCST-type phase behavior or did not phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The phase homogenization temperature caused by the upper critical solution temperature (UCST) type phase behavior was measured by an annealing technique to access the closest true equilibrium temperature. [26][27][28][29][30][31] Changes in morphology of blends with temperature were also observed by an image analyzer [Bummi Universe, model:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase homogenization temperature caused by the upper critical solution temperature (UCST) type phase behavior was measured by an annealing technique to access the closest true equilibrium temperature. [26][27][28][29][30][31] Changes in morphology of blends with temperature were also observed by an image analyzer [Bummi Universe, model:…”
Section: Methodsmentioning
confidence: 99%
“…Phase homogenization temperatures of blends caused by UCST-type phase behavior were measured by an annealing technique. [26][27][28][29][30][31] For exam- (Figure 4(a)) was heated rapidly to a temperature about 200 o C and then heated at a rate of 5 o C/min. As shown in Figure 4(b), blend became transparent and changes in the image were observed at 265 o C. Note that phase separation occurred again when homogeneous blend at 265 o C was cooled to 255 o C at a rate of 5 o C/min (Figure 4(c)).…”
Section: Mw Mnmentioning
confidence: 99%
“…Even more, from the comparison of the Flory-Huggins interaction parameter obtained for a polyethylene-polypropylene blend with the χ -parameter obtained for the homologous block copolymer, extracted from order-disorder transition temperature (TODT) data, they concluded that the current theories cannot account for both homopolymer blend and block copolymer phase behaviors. [5] The lattice theory of Sanchez-Lacombe (SL) [6,7] has been applied extensively to both homopolymers blends [8][9][10][11][12] and copolymers [13][14][15] using pressure-volume-temperature (PVT) data to determine the interaction parameter. In the framework of this theory, scaling parameters of pure components are obtained by fitting PVT data, while model parameters of miscible mixtures or block copolymers are calculated by using mixing rules as a function of lattice-binary interaction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, phase behavior of ternary blends composed TMPC, DMPC, and SAN was explored and then their miscibility was compared with that of binary blend. Based on the volume fluctuation thermodynamics [15,19], the phase stability of polymer mixtures was analyzed to understand the differences in the phase behavior of binary and ternary blends having the same chemical components and compositions.…”
Section: Introductionmentioning
confidence: 99%
“…(7). As described in the volume fluctuation thermodynamics [15,19], the addition of component, i.e. the additional degree of freedom accompanied by the asymmetry in the binary interactions, for ternary blends results in the destabilization even though entropy and energetic terms for the ternary are more favorable for miscibility than those of binary mixture.…”
mentioning
confidence: 97%